Let us first define Hypotenuse Leg (HL) congruence theorem:
<em>If the hypotenuse and one leg of a right angle are congruent to the hypotenuse and one leg of the another triangle, then the triangles are congruent.</em>
Given ACB and DFE are right triangles.
To prove ΔACB ≅ ΔDFE:
In ΔACB and ΔDFE,
AC ≅ DF (one side)
∠ACB ≅ ∠DFE (right angles)
AB ≅ DE (hypotenuse)
∴ ΔACB ≅ ΔDFE by HL theorem.
Answer:
x = -2
Step-by-step explanation:
For this problem, we must simply solve for x. To do this, we will need equation operations, and the use of the distributive property.
Let's work this line by line until we have the value for x:
3{-x + (2x + 1)} = x - 1
3*-x + 3*(2x + 1) = x - 1
-3x + 6x + 3 = x - 1
3x + 3 = x - 1
2x = -4
x = -2
Now we can check our answer for x by plugging back into the original equation and see if the left hand side is equal to the right hand side:
3{-x + (2x + 1)} = x - 1
3{-(-2) + (2(-2) + 1)} ?= (-2) - 1
3{2 + (-4 + 1)} ?= -3
3{2 + (-3)} ?= -3
3{-1} ?= -3
-3 == -3
Thus, we have found the solution for x to be equivalent to negative 2.
Cheers.
Answer:Davinki
Step-by-step explanation:made the mona lisa
Answer:
12
Step-by-step explanation: